(untitled) (Revista Brasileira Multidisciplinar, 2020)
Rotavirus infection, which is directly related to the population’s quality of life, can culminate in death, mainly of children. This review discusses the prevalence and distribution of rotavirus genotypes, focusing on the genotypic variation of the virus after the implementation of vaccines and the cross-infection between animal and human species. It was searched the published literature from January 2006 to July 2017 using the Web of Knowledge database and the search terms “rotavirus”, “genotype”, “prevalence post vaccine”, and “emerging genotypes”. It was observed that the predominant genotypes changed in all continents, and that some genotypes are still emerging. Two hypotheses for this global change are the genetic variability of the virus and the emergence of vaccine-resistant genotypes. In addition, the virus can easily infect several animal species other than humans, as evidenced by reports of cross-infection of strains, which have served as warning for the generation of new virus genotypes. Inter-sectoral actions that encompass not only the health sector, but also all the socio-economic sector including the government, researchers, teachers, health agents, and communities contribute to decrease health-related expenditures and reduce mortality caused by the rotavirus, thereby improving health indicators and promoting health around the world.